PENGARUH KEPEMILIKAN MANAJERIAL, KUALITAS AUDIT DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Rahman, Kristanti; Mardiyah, Aniza Husniatul (JURNAL EKONOMI, 2022)
This study aims to analyze the Effect of Managerial Ownership, Audit Quality, and Leverage on the Integrity of Financial Statements (Study on Islamic Commercial Banks Registered with the Financial Services Authority for the Period 2016-2020). The population of this study is Sharia Commercial Banks Registered with the Financial Services Authority (OJK) for the 2016-2020 period. Technical sampling using purposive sampling. The type of data used is secondary data and obtained 6 Sharia Commercial Banks which are used as samples. Statistical analysis in this study used multiple linear regression. The results of this study show that: Managerial Ownership does not affect the Integrity of Financial Statements, Audit Quality affects the Integrity of Financial Statements, Leverage affects the Integrity of Financial Statements. The suggestion of this study, for the researcher can then replace the object of research, add the latest research period, add other independent variables, such as institutional ownership, liquidity, audit committee and auditor independence.